German case study report - Weigel, Tanja [Verfasser] (My University, 2012)
"In Germany regulation of traineeships is largely restricted to those schemes which are training related, and as such, are covered by the Federal Vocational Training Act (Berufsbildungsgesetz). At present, of particular interest in Germany is how far the new Bologna-Structure of Higher Education causes substitution effects in recruitment at the cost of recruitment from the vocational education sector. Therefore, the aim of the German case study is to investigate whether the 'package' of Bachelor's degree plus traineeships might develop as an alternative to the dual system for clerical or technical occupations." (Autorenreferat; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; S 2.3 Berufsbildungspolitik; I 2.2 Europa; S 1.6.1 Praktika; Bologna-Prozess; Hochschulbildung; Bachelor; Betriebliche Berufsausbildung; Substitutionseffekte; Bundesrepublik Deutschland